THU0229 Treatment of six patients with adult onset of still´s disease with infliximab. (1st June 2001) - Kraetsch, HG; Antoni, C; Dechant, C; Kalden, JR; Manger, B
Abstract : Background: TNF-blocking agents, like the chimeric monoclonal antibody cA2, infliximab, have been effective in several double-blind trials in RA. Objectives: The efficacy of infliximab therapy was tested in patients with severe, active adult onset Still's disease (AOSD) despite conventional immunosuppressive therapy. Methods: In 6 patients with AOSD according to the Yamagushi criteria of 1992, a therapy with infliximab was started. Malignant and infectious diseases or other inflammatory rheumatic diseases had been excluded. All patients had severe disease with high clinical and serological activity and had initially been treated with high-dose steroids. Patient 1 had a history of 3 years of AOSD with fever, chills, pleural and pericardial effusions and hepatosplenomegaly and had previously been treated with methotrexat and azathioprine. Despite of this, he developed increasing serological signs of inflammation and arthritis of both hips and peripheral joints. The second patient had a history of 5 years of AOSD with oligoarthritis, myalgias and recurrent fever despite of treatment with azathioprine, methotrexat, first administered alone, then in combination with cyclosporine A and cyclophosphamide pulse therapy. The other four patients had an earlier stage of their disease and did not have prior DMARD treatment apart from the initial steroid therapy. All of our patients with AOSD had polyarthralgias, splenomegaly, continuing fever, leukocytosis, elevated CRP, ESR and ferritin levels. Five patients showed the typical rash, and 3 had polyarticular synovitis. The attempt to reduce immunosuppressive treatment caused a relapse of the disease in all of our patients. All patients received 5 mg/kg infliximab at week 0, 2, and 6. Thereafter infliximab infusions were continued at intervals of 6 to 8 weeks depending on the patient's individual disease activity. Results: In all patients, fever, arthralgias, myalgias, splenomegaly and the rash resolved within the first three courses of treatment with infliximab. All serological parameters (CRP, ESR, hyperferritinaemia) returned to normal values. After three courses of infliximab infusions, splenomegaly could not be detected in any of our patients. One patient had still severe pain in the left hip, caused by hip postarthritic osteoarthrosis, requiring hip replacement. Up to now, our patients have been treated between 2 and 18 months. Throughout this treatment period all patients continued to benefit from this therapy with regard to their clinical symptoms, their joint counts and their serological disease activity. One of our patients experienced a moderate infusion reaction during the second treatment. The infusion was discontinued for one hour and could be resumed after that without any problems. Conclusion: In conclusion, all 6 patients with AOSD showed marked improvement of the disease after treatment with infliximab, also in an early stage of AOSD. Our preliminary data suggest the potential therapeutic benefit of anti-TNF treatment in AOSD.